At-Point Clinical Frailty Scale as a Universal Risk Tool for Older Inpatients in Acute Hospital: A Cohort Study - Jung, Hee-Won; Baek, Ji Yeon; Kwon, Young hye; Jang, Il-Young; Kim, Dae Yul; Kwon, Hyouk-Soo; Lee, Sun hee; Oh, Hyun jin; Lee, Eunju; Koh, Younsuck (Frontiers in Medicine, 2022)
Background While the Clinical Frailty Scale (CFS) has been extensively validated for predicting health outcomes in older adults, the role of the at-point CFS at the time of examination is unclear. We aimed to examine the ability of at-point CFS for predicting clinical outcomes of older inpatients. Methods As a single center and prospective cohort study, we enrolled 1,016 older adults who were 65 years or older, and admitted to one of 9 medical or surgical units from May 2021 to September 2021. The associations of the at-point CFS with outcomes of falls, delirium, pressure ulcers, 30-day unplanned readmission and/or emergency department (ED) visit, institutionalization, and a composite outcome, were analyzed. Results In the study population (n = 1,016), 26 had incident pressure ulcers, 6 had falls, 50 experienced delirium, and 13 died during hospitalization. Also, 37 experienced an ED visit, and 22 had an unplanned readmission within 30 days after discharge. The composite outcome was 1·7% among patients with CFS <5 and 28·5% with CFS ≥ 5. A higher CFS was associated with an increased risk of a fall (odds ratio [OR] 1.74 [1.01 – 3.01]), pressure ulcer (OR 3.02 [2.15 – 4.23]), delirium (OR 2.72 [2.13 – 3.46]), 30-day readmission (OR 1.94 [1.44 – 2.62]), ED visit (OR 1.81 [1.47 – 2.23]), death (OR 3.27 [2.02 – 5.29]), and institutionalization after discharge (OR 1.88 [1.62 -2.18]). Conclusion The at-point CFS assessed in older inpatients can screen high-risk individuals who might experience adverse geriatric conditions and in-hospital outcomes. .